ACUTE TOXICITY AND DIURETIC ACTIVITY OF MIMUSOPS ELENGI EXTRACTS - R G KATEDESHMUKH; R V SHETE 2, K V OTARI; K V OTARI; M Y BAGADE; A PATTEWAR (International Journal of Pharma and Bio Sciences, 2010)
Kidney, as excretory organ of our body serves important function of excretion of waste products, regulation of fluid volume and electrolyte content etc. Damage to kidney can lead to severe life threatening complications. Diuretics are drugs capable of increasing levels of urine. The ethyl acetate, ethanol and water extract of Mimusops elengi was evaluated for diuretic activity. Mimusops elengi an herb traditionally claimed to diuretic potential and being used for kidney complications from centuries. Diuretic study was carried out in rodents by measuring the urine volume at 1, 2, 4, 6 and 24 hrs. The extracts were administered orally at the dose of 250 mg/kg b.w. Na+/ K+ ratio was higher in aqueous extract and followed by ethanol and ethylacetate extracts. The aqueous extracts showed a significant diuretic activity when compared with other extracts. From results it can be concluded that all the extracts tested have a diuretic potential.